1998
DOI: 10.1071/s98029
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of soil nutrients around nest entrances of the funnel ant Aphaenogaster barbigula (Myrmicinae) in semi-arid eastern Australia

Abstract: The distribution of soil nutrients around nest entrances of the ant Aphaenogaster barbigula was studied in a semi-arid woodland in eastern Australia. The ants re-excavate their nest chambers after rainfall, trapping any litter which falls near the entrance, and blocking the passage of litter moving downslope by processes of overland flow. The entrapment of organic matter around nest entrances resulted in significantly higher levels of nitrogen, organic matter, and some cations compared with nest-free surfaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…2005; Azcarate and Peco 2007; table 1). Only, the study of Eldridge and Myers (1998), who worked with nests of Aphaenogaster barbigula , showed lower K levels in the surface soil of nests. However, in the subsoil of the nest they also detected higher K levels compared to the control, whereas Nkem et al.…”
Section: Ants and Soil Properties: Fine Scale Effectsmentioning
confidence: 95%
See 3 more Smart Citations
“…2005; Azcarate and Peco 2007; table 1). Only, the study of Eldridge and Myers (1998), who worked with nests of Aphaenogaster barbigula , showed lower K levels in the surface soil of nests. However, in the subsoil of the nest they also detected higher K levels compared to the control, whereas Nkem et al.…”
Section: Ants and Soil Properties: Fine Scale Effectsmentioning
confidence: 95%
“…(1996) specified that only open nest entrances of Lasius neoniger nests contributed to enhanced infiltration in Sparta soils located in the lower Wisconsin river valley (USA), and that many nest entrances were closed during rainfall events, re‐opening within 2 h after the event. Eldridge and Myers (1998) suggested that increased infiltration rates in nest entrances of Aphaenogaster barbigula also facilitated the entrapment of plant leaves, an important food resource, that are transported by overland flow. In contrast to these studies, Sarr et al.…”
Section: Ants and Soil Properties: Fine Scale Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ants are important ecosystem engineers and perform functional roles that strongly influence invertebrate (Carroll & Janzen 1973;Laakso 1999) and plant (Briese 1982;Samson et al 1992) assemblages, seed dispersal (Handel & Beattie 1990;Ness et al 2004), and soil conditions (Eldridge & Myers 1998;Lobry de Bruyn 1999). Ants are responsive to disturbance and have been widely used as bioindicators in various environmental assessments such as fire, mining and grazing (reviewed by Hoffmann & Andersen 2003).…”
Section: Introductionmentioning
confidence: 99%